2000
DOI: 10.1016/s0399-1784(00)00126-2
|View full text |Cite
|
Sign up to set email alerts
|

Suspended sediments in a macrotidal estuary: comparison and use of different sensors

Abstract: Measurements made using an in situ particle-sizer (PSA) were compared to those of an optical backscatter sensor (OBS) in a macrotidal estuary. Both estimate the total volume of particles. After comparison with dry weight of suspended matter sampled in the study area, the different measurements were converted into dry weight. In three different kinetic energy regimes, times series were coherent for most of the observations. Discrepancies of suspended sediment concentrations estimated by both sensors appeared un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…In two previous studies (Gentien et al, 1995;Lunven & Gentien, 2000), we have reported cases where large organic aggregates presumably introduced biases in measurements of particle population distribution. Sampling of these aggregates being very difficult, confirmation of their occurrence can only be performed through direct video observation.…”
Section: Introductionmentioning
confidence: 91%
“…In two previous studies (Gentien et al, 1995;Lunven & Gentien, 2000), we have reported cases where large organic aggregates presumably introduced biases in measurements of particle population distribution. Sampling of these aggregates being very difficult, confirmation of their occurrence can only be performed through direct video observation.…”
Section: Introductionmentioning
confidence: 91%
“…Lunven and Gentien 2000;Lunau et al 2006;Mietta et al 2009). In estuaries, the high variability in forcing (Verney et al 2009) and the impact of biological factors make the behaviour of cohesive sediments even more complex and still not well understood (Winterwerp 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The advent of optical backscatter sensors (Bunt et al 1999;Lunven and Gentien 2000) and acoustic Doppler profilers (Land and Bray 1998;Holdaway et al 1999;Hoitink and Hoekstra 2005;Kostaschuk et al 2005) has enabled the acquisition of much longer time series of suspended sediment concentration (SSC) than would be possible by discrete sampling. Interpreted with care, long-term SSC time series provide valuable insights into the processes controlling sediment regime (Schoellhamer 1996(Schoellhamer , 2002 and, importantly, allow the evaluation of hypotheses originating from quantitative determinations of the residual flux.…”
mentioning
confidence: 99%